Modelo para processo de desenvolvimento de software a partir da engenharia de requisitos: uma proposição orientada às empresas do APL de TI do sudoeste do Paraná - Santos, Ivânia Ramos dos (2016)
The quality of the software product has been linked to the quality of its development process. There are several models and quality standards, which can be used for small software companies, from which it is understood that the defined processes according to these models can anticipate their results. One of the key processes for quality is related to software requirements, including the definition of requirement, from the user point of view, the software maintenance, with traceability throughout the lifecycle and its production process, and that the study of the Requirements Engineering fields. The Innovation plays an important role in the development of software, the product and the use of technologies and technical and managerial procedures to ensure quality and minimize resources, cost and time. Based on these, this work proposes a model for innovation in the software development process, with emphasis on Requirements Engineering, oriented to the context of the Local Productive Arrangement IT Paraná Southwest. The grouping of micro and small enterprises or other forms of organization, brings the benefits of resource sharing, experiences, skilled labor, marketing strategies, training activities and consulting. However, only be part of these groups is not enough to ensure the software development, especially small companies, expansion and even the market kept. Competitiveness is also associated with reduced resources and production time, goods and services the supply, that meet established quality criteria. The proposed model was constructed from an action research, of qualitative approach, involving bibliographical basis and multicases study of five companies that Cluster. The multicases study identified needs and problems of companies about the Software Development Process (SDP), to be supplied with the model; and action research possible fit, detail and validate this model. The pattern defines a process model that specializes when performing each software project, the necessary adjustments to the project context. The results of this research sought to present application of technical alternatives to meet quality criteria, aligned to RE and quality models. The work also presents alternatives to adapt to Cluster companies.